Efficacy of antioxidants in experimental mycotoxicoses of broilers-A pathomorphological study of lymphoid organs - KUMAR, B SANTHOSH; VIJYASARTHI, S K; Gajendragad, M; Rao, Sugna; NARAYANASWAMY, H D (The Indian Journal of Animal Sciences, 2005)
The efficacy of supplementing combined antioxidants (CAO) such as a vitamin E and selenium in the amelioration of experimental aflatoxicosis, ochratoxicosis and their combined toxicosis in broiler chicks was studied. Day-old commercial chicks (144) were randomly divided into 8 groups each containing 18 chicks. Birds fed with aflatoxin (AF), ochratoxin (OA) and their combination manifested clinical signs of dullness, ruffled feathers, huddling, listlessness, reduced feed consumption, stunted growth, polydypsia and diarrhoea. Whereas, the bird fed with toxin containing diet and also supplemented with CAO showed clinical signs of less severity which included reduced feed intake, poor growth and listlessness. The birds of group I (untreated control) and group 2 (CAO supplemented) were healthy and did not show any clinical signs throughout the study. Pathomorphological changes in the toxin fed birds included atrophy ofspleen, bursa of Fabricius and thymus, whereas caecal tonsils appeared normal. The birds which were fed with AF, OA nnd their combination and also supplemented with CAO showed similar gross lesions but were of lesser intensity. Histologically, the lynlphoid organs revealed congestion, haemorrhages, sparse cellularity of follicles, lymphocytolytic activity and presence of histlocytes in toxin fed birds. Birds which received CAO along with toxins in the diet showed mild degree of lymphocytolytic activity in thymus. However, bursa OF Fabricius showed lymphoid hyperplasia with formation of giant follicles. In addition, spleen revealed formation of additional follicles with large number of lymphoblasts. The caecal tonsils appeared normal microscopically on the the days irrespective of the dietary treatment. Supplementation of CAO to the birds whicli were fed with AF, OA either alone or in combination showed near normal lymphoid organs as compared to corresponding toxin alone treated birds.